Differential OER Impacts of Formal and Informal ICTs: Employability of Female Migrant Workers - Chib, Arul; Wardoyo, Reidinar Juliane (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Information and communication technologies aid marginalized groups in seeking social support, building proximate networks, and improving employment opportunities. However, one key factor that is understudied in the literature is the impact of open education resources (OER) on the employability of marginalized groups. This study focuses on open and distance learning in the context of low-income female migrant domestic workers as a marginalized community. Specifically, we assessed the differential effects of two types of communication: informal OER resources (e.g., social media, mobile calling, texting) and formal OER resources (e.g., classroom prescribed learning tools and lectures) on specific development outcomes of functional literacy and perceived employability. A survey was conducted amongst female migrant domestic workers (n=100) enrolled in the Indonesian Open University in Singapore. Results indicate that access to OER resources via computers in the formal context of institutional learning, when combined with employability awareness, had a significant influence on livelihood outcomes, i.e., perceived employability. However, this did not lead to actual improvements in learning – functional literacy. Instead, actual learning improvement was influenced by digitals skills enabled by mobile phones and computers. The study concludes with a discussion on the policy implications for digital skills training via mobile devices for marginalized populations to bolster the positive effects of OER on livelihood outcomes.